2017
DOI: 10.1177/0379572117708647
|View full text |Cite
|
Sign up to set email alerts
|

Rich Food Biodiversity Amid Low Consumption of Food Items in Kilosa District, Tanzania

Abstract: Despite the rich local food biodiversity, households relied on few food items which may be due to limited awareness and knowledge about the biodiversity of foods in the community. It is important to educate communities on the rich and affordable food base available locally to improve their food diversity, income, and nutritional status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…The authors also showed an insufficient intake of minerals in comparison to recommended daily intakes, and a low food diversity among these farmers despite a rich bio-diversity and food availability (e.g., fruits and vegetables) in Kilosa and neighbouring districts. The dominance of a cereal-based diet with insufficient fruit and vegetable consumption despite the rich local food biodiversity is well known in rural areas of Tanzania [52,53].…”
Section: Discussionmentioning
confidence: 99%
“…The authors also showed an insufficient intake of minerals in comparison to recommended daily intakes, and a low food diversity among these farmers despite a rich bio-diversity and food availability (e.g., fruits and vegetables) in Kilosa and neighbouring districts. The dominance of a cereal-based diet with insufficient fruit and vegetable consumption despite the rich local food biodiversity is well known in rural areas of Tanzania [52,53].…”
Section: Discussionmentioning
confidence: 99%
“…Diet diversity can be measured by counting individual foods, food groups or foods within a group, and can be measured over a time period ranging from the previous 24 hours (24‐hour recalls) or over a 7‐day period to intake over one year. Food intake data may be collected once or a number of times as summarized in Table a‐d. Factors that should be considered when measuring diet diversity are summarized in Table .…”
Section: Methodsmentioning
confidence: 99%
“…There is a nonexhaustive list of factors that may affect allergy outcomes, but potential confounders should be corrected for analysing associations between diet diversity and allergy outcomes Diet diversity can be measured by counting individual foods, 31,37,[42][43][44][45][46] food groups 30,[34][35][36]38,39,41,43,[47][48][49][50][51][52][53][54] or foods within a group, 32,33,55,56 and can be measured over a time period ranging from the previous 24 hours (24-hour recalls) [31][32][33][34][35]38,40,44,46,48 or over a 7day period 33,39,42,47,53,[55][56][57] to intake over one year. Food intake data may be collected once [32][33][34]…”
Section: Recall Periodmentioning
confidence: 99%
“…Several studies have observed the higher consumption of wild foods during the agricultural off-season (e.g. Ntwenya et al, 2017;Cruz-Garcia and Price, 2011), and as coping mechanisms at times of anticipated food shortage (Guyu and Muluneh, 2015;Hunter et al, 2015;Noromiarilanto et al, 2016). For example, Rakatobe et al (2016) observed that the harvest of wild foods, especially wild yams, is an important way that the Madagascan Malagasy prepare for cyclone activity.…”
Section: Indigenous Peoples' Food Systems Provide Nourishment and Hea...mentioning
confidence: 99%